Sub-terahertz, Microwaves and High Energy emissions during the 6 December 2006 flare at 18:40 UT - Kaufmann, Pierre (2009)
The presence of a solar burst spectral component with flux density increasing with frequency in the sub-terahertz range, spectrally separated from the well-known microwave spectral component, bring new possibilities to explore the flaring physical processes, both observational and theoretical. The solar event of 6 December 2006, starting at about 18:30 UT, exhibited a particularly well-defined double spectral structure, with the sub-THz spectral component detected at 212 and 405 GHz by the Solar Submilimeter Telescope (SST) and microwaves (1∈-∈18 GHz) observed by the Owens Valley Solar Array (OVSA). Emissions obtained by instruments onboard satellites are discussed with emphasis to ultra-violet (UV) obtained by the Transition Region And Coronal Explorer (TRACE), soft X-rays from the Geostationary Operational Environmental Satellites (GOES) and X- and γ-rays from the Ramaty High Energy Solar Spectroscopic Imager (RHESSI). The sub-THz impulsive component had its closer temporal counterparts only in the higher energy X- and γ-rays ranges. The spatial positions of the centers of emission at 212 GHz for the first flux enhancement were clearly displaced by more than one arc-minute from positions at the following phases. The observed sub-THz fluxes and burst source plasma parameters were difficult to be reconciled with a purely thermal emission component. We discuss possible mechanisms to explain the double spectral components at microwaves and in the THz ranges.